Ankylosing spondylitis is associated with the anthrax toxin receptor 2 gene (ANTXR2) - Karaderi, T; Keidel, S; Pointon, J; Appleton, L; Brown, M; Evans, D; Wordsworth, B (BMJ Publishing Group, 2014)
Objectives ANTXR2 variants have been associated with ankylosing spondylitis (AS) in two previous genome-wide association studies (GWAS) (p∼9×10-8). However, a genome-wide significant association (p<5×10-8) was not observed. We conducted a more comprehensive analysis of ANTXR2 in an independent UK sample to confirm and refine this association.